The experiences and views of elementary school teachers regarding mobbing - Yeliz Temli Durmuş (Journal of Pedagogical Research, 2023)
The aim of this phenomenological study was to determine the experiences and views of elementary school teachers about mobbing. To address this issue, the researcher conducted semi-structured interviews with 20 female and 19 male elementary school teachers working in public elementary schools. Four themes emerged during the analysis: reasons for mobbing, experiences of mobbing, struggling with mobbing, and consequences of mobbing. These themes, along with their corresponding categories and codes, were identified through a collaborative effort between two researchers. The codes associated with these themes include limitation in expressing one's experiences of mobbing, failure to respond to the mobber's inappropriate behavior and inability to substantiate these actions, and non-membership in an educational union, which motivates mobbers to persist in their harmful behaviors. The study concluded with a number of recommendations for future studies.